2021
DOI: 10.21203/rs.3.rs-648608/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct Phyllosphere Microbiome of Wild Tomato Species in Central Peru Upon Dysbiosis

Abstract: Plants are colonized by myriads of microbes across kingdoms, which affect host development, fitness and reproduction. Hence, plant microbiomes have been explored across a broad range of host species, including model organisms, crops and trees under controlled and natural conditions. Tomato is one of the world’s most important vegetable crops, however little is known about the microbiota of wild tomato species. To obtain insights into the tomato microbiota occurring in natural environments, we sampled epiphytic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 96 publications
(123 reference statements)
0
1
0
Order By: Relevance
“…Plant species is a distinctive factor known to influence rhizosphere and phyllosphere communities ( Costa et al, 2006 ; Xiong et al, 2021 ). Although phylogenetically similar hosts tend to harbor similar core sets of microbes ( Lajoie and Kembel, 2021 ) there are distinctive differences across plant species ( Pendergast et al, 2013 ; Laforest-Lapointe et al, 2016 ; Runge et al, 2021 ). For example, a recent study found that two closely related tree species ( Acacia heterophylla A. koa ), which speciated 1.4 million years ago have distinct microbiomes with a similar “core” of associated rhizosphere taxa ( Le Roux et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plant species is a distinctive factor known to influence rhizosphere and phyllosphere communities ( Costa et al, 2006 ; Xiong et al, 2021 ). Although phylogenetically similar hosts tend to harbor similar core sets of microbes ( Lajoie and Kembel, 2021 ) there are distinctive differences across plant species ( Pendergast et al, 2013 ; Laforest-Lapointe et al, 2016 ; Runge et al, 2021 ). For example, a recent study found that two closely related tree species ( Acacia heterophylla A. koa ), which speciated 1.4 million years ago have distinct microbiomes with a similar “core” of associated rhizosphere taxa ( Le Roux et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%